G175 "learning together": do integrated child health clinics educate and improve outcomes?. (27th April 2015) - Macaulay, CP; Sherwood, E; Riches, W; Lakahanpaul, M; Spicer, J
Abstract : Background: A significant number of children seen within secondary care, both in emergency departments, and also in out-patients, could be seen within a primary care setting (Saxena 2009, Milne 2010). Currently general paediatric postgraduate training programmes are focused on training paediatricians almost exclusively in hospital-based systems. RCGP data (2012) reports that fewer than half of general practitioners (GPs) in training currently have an opportunity to gain experience of acute childhood illness in a specialist-based training placement, while RCPCH data (2007) suggests that only 50–60% of qualified GPs have had any formal paediatric training. The educational model of Learning Together clinics was therefore developed to address these challenges and improve training in community child health for GP and Paediatric trainees. Intervention: "Learning Together clinics": child health clinics within a primary care setting, were launched in 40 sites across London. Each clinic site provided joint training with Paediatric and GP registrars seeing children together. Patients were discussed after the clinics in multidisciplinary practice team meetings to allow for clinical continuity and cascading learning to other health professionals. Evaluation: A combination of methods were used including: Pre and post intervention registrar surveys (n = 300) Case log analysis (n = 683) Surveys with families after clinics (n = 351) Follow up phone surveys with families (n = 125) Registrar focus groups (n = 19) Audit of practice notes (n = 22) Results: Over the 6 month pilot funded by HECL through UCLP, 848 children were seen in 145 LT clinics 37 Paediatric Registrars and 40 GP Registrars made up 44 pairs in 40 GP practices 99% of 351 parent forms said they had a good experience of care. 87% of parents reported increased confidence to manage their child's health. Trainees reported a good learning experience and change in behaviour as a result of the clinics Trainees reported that 55% of Learning Together appointments resulted in an avoided referral or A&E visit A notes audit of 22 practices before, during and after the clinics suggests that there is better adherence to National Guidance for common childhood conditions as a result of the clinics. Implications: Learning together clinics are a valuable educational training model: they are feasible and economically viable. A further study is being led by South London to broaden the impact of the programme and further evaluate clinical outcomes